The Irony of Humanization: Alemtuzumab, the First, But One of the Most Immunogenic, Humanized Monoclonal Antibodies - Baker, David; Ali, Liaqat; Saxena, Gauri; Pryce, Gareth; Jones, Meleri; Schmierer, Klaus; Giovannoni, Gavin; Gnanapavan, Sharmilee; Munger, Kathleen C.; Samkoff, Lawrence; Goodman, Andrew; Kang, Angray S. (Frontiers in Immunology, 2020)
Alemtuzumab was designed to reduce the immunogenicity of the parent, CD52-specific, rat immunoglobulin. Although originally marketed for use in cancer (Mabcampath®), alemtuzumab is currently licensed and formulated for the treatment of relapsing multiple sclerosis (Lemtrada®). Likely, due to its history as the first humanized antibody, the potential of immunogenicity of the molecule has been considered inconsequential, and anti-drug anti-drug antibodies (ADA) responses were similarly reported as being clinically insignificant. Nonetheless, despite humanization and depletion of peripheral T and B cells, alemtuzumab probably generates the highest frequency of binding and neutralizing ADA of all humanized antibodies currently in clinical use, and they occur rapidly in a large majority of people with MS (pwMS) on alemtuzumab treatment. These ADA appear to be an inherent issue of the biology of the molecule and, importantly, the target, such that avoidance of immunogenicity related-effects may have driven the dosing-schedule in clinical practice. At the population level this enables the drug to work in most pwMS, but in some individuals level, as we show here, antibody neutralization appears to be sufficiently severe to reduce efficacy and allow disease-breakthrough. It is therefore imperative that efficacy of lymphocyte depletion and the anti-drug response is monitored in people requiring additional cycles of treatment, notably following disease breakthrough. This may help inform whether to re-treat or switch to another disease modifying treatment.